Generation of the Early Cretaceous granitoid in the Dazeshan region, Jiaodong Peninsula: Implications for the crustal reworking in the North China Craton - Dong, Leilei; Yang, Zhiming; Bai, Xin; Deng, Chen (Frontiers in Earth Science, 2023)
Lower crust derived granitic rocks provide constraints on the crustal reworking process and consequently give hints on the destruction mechanism of the cratons. The North China Craton (NCC) underwent extensive crustal melting in the Mesozoic. Here in this study, we investigate granitic intrusions in the Dazeshan region of the Jiaodong Penisular. Whole-rock major and trace element analyses and zircon U-Pb ages coupled with Hf isotopes are used to reveal the crustal reworking processes. Zircons separated from the quartz porphyry, Linglong granite, rhyolite porphyry and the biotite granite give weighted mean 206Pb-238U ages of 119.2 ± 1.0 Ma, 140.2 ± 1.0 Ma, 120.6 ± 0.5 Ma, and 119.9 ± 0.7 Ma, respectively. The quartz porphyry, rhyolite porphyry and the biotite granite have high silica contents (SiO2 = 74–77 wt.%) but low MgO, Co and Ni concentration. Calculated εHf(t) for the rhyolite porphyry and the biotite granite range from -18.3 to -20.0 and -17.8 to -20.2, respectively. These geochemical features imply an ancient crust sources. The quartz porphyry has distinct primitive mantle normalized rare earth element (REE) patterns and is characterized by lower ΣREE contents and lack of pronounced negative Eu anomaly. Whole-rock and zircon Dy/Yb ratios show no correlation with whole-rock Rb/Sr ratios and zircon Hf contents, reflecting little effect of crystal fractionation. The Ba/La ratios are also high (>150), but the Sr/Y and La/Yb ratios are low (Sr/Y<50; La/Yb<15). These features probably indicate the quartz porphyry was generated by water-fluxed melting without differentiation. The rhyolite porphyry and the biotite granite share many geochemical similarities, denoting a unified source. High La/Yb (>30) but low Sr/Y (<20) ratios and apparent negative Eu anomalies indicate the fractionation of plagioclase. Zircon Dy/Yb decrease with rising Hf concentrations, reflecting noticeable amphibole fractionation. These two suites have fairly low Ba/La ratios. These data together point towards an identical source: dehydration melting of a relatively thickened crust. These melts experienced crystal fractionation after extraction. We propose that the intrusions were generated by underplating of water rich mafic magma, which provides both fluid and heat and finally induces two kinds of styles of melting.